The Attitude of Farmers to the Agricultural Extension Professional and its Relationship with Participation in the Agricultural Extension Program in Nagari Air Gadang, Pasaman District, West Pasaman Regency - Gustia Yanti; Tasril Bartin (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2021)
This research was motivated by the high participation of participants in participating in agricultural extension programs in Nagari Air Gadang, Pasaman District, West Pasaman Regency. It is suspected that the cause of the high participation of participants in the agricultural extension program was the good attitude of the participants in the agricultural extension program. This research was conducted to: 1) describe the attitude of farmers towards the agricultural extension profession, 2) describe the participation of participants in the agricultural extension program, 3) see the relationship between farmers' attitudes towards the agricultural extension profession and its relationship with participation in the agricultural extension program in Nagari Air Gadang, Pasaman District, West Pasaman Regency. This research is correlational quantitative. The population in this study were all members of the group of young unified farmers, amounting to 52 people and 34 people who were sampled by using data collection techniques using a questionnaire, the data obtained were analyzed using descriptive analysis and the product-moment correlation formula. The results of this study indicate: 1) the attitude of farmers towards the agricultural extension profession is categorized as very high; 2) the participation of the participants in the agricultural extension program was categorized as very high; 3) there is a very significant relationship between farmers' attitudes towards the agricultural extension profession and its relationship with participation in the agricultural extension program in Nagari Air Gadang, Pasaman District, West Pasaman Regency. The research suggestions are: 1) it is hoped that the government of Nagari Air Gadang, Pasaman District, West Pasaman Regency, to be able to pay attention to and support the businesses carried out by its community groups; 2) it is hoped that young farmer groups will unite to further increase their participation in participating in agricultural extension programs in order to obtain maximum results; 3) It is hoped that the next researcher will be able to find or find other variables that affect the participation of participants in participating in the agricultural extension program..Keywords: Farmer's Attitude, Extension Profession, Participation, Agricultural Extension